The Implementation of Learning of Islamic Characters in Ma’had Al-Jami’ah IAIN Samarinda, Indonesia - Rahma Fitria Purwaningsih; Fathul Jannah (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2021)
Indonesia is currently facing degradation of character marked by deviations of norms that are social and religious. Ma'had Al-Jami'ah is responsible for improving the character and create who are intellectually religious. This study aims to find out the implementation of learning of Islamic characters in Ma'had Al-Jami'ah IAIN Samarinda. This research used descriptive qualitative and collected data by interviews, observation, and documentation. The results showed that Text learning in religious activities still uses classical models in large numbers, so text learning has not achieved maximum results. Moreover, Islamic learning activities are still limited to translating and have not yet achieved scientific activities following university students' capacity. The learning implementation of Islamic character has been successful in three Islamic scopes, both in ḥabl minallāh, min al-nās, and min al-'ālam. Although ḥabl minallāh has not reached the level of maḥabbah, the learning process has trained students to worship and become obedient servants. Concerning the various learning activities and processes available, ḥabl min al-nās have become the most dominant scope, especially in attitude (adab) and empathy. Meanwhile, ḥabl min al-'ālam is only limited to cleaning activities and has not reached the stage of iḥsan comprehension.